2020
DOI: 10.1111/1462-2920.15194
|View full text |Cite
|
Sign up to set email alerts
|

Multiple environmental parameters impact lipid cyclization in Sulfolobus acidocaldarius

Abstract: Adaptation of lipid membrane composition is an important component of archaeal homeostatic response. Historically, the number of cyclopentyl and cyclohexyl rings in the glycerol dibiphytanyl glycerol tetraether (GDGT) Archaeal lipids has been linked to variation in environmental temperature. However, recent work with GDGT-making archaea highlight the roles of other factors, such as pH or energy availability, in influencing the degree of GDGT cyclization. To better understand the role of multiple variables in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 41 publications
9
32
1
Order By: Relevance
“…While there is broad consensus on the optimal growth temperature of S. acidocaldarius being at 75 °C [ 7 , 8 , 9 , 10 , 33 ] the described optimal cultivation pH still varies [ 5 , 6 , 7 , 8 , 9 , 10 ]. Our study determined a pH optimum of 3.0 in regards to the cell density during continuous cultivation ( Figure 2 ), contradicting the recent publication by Cobban et al [ 11 ], in which higher biomass yields were observed at pH 2.0 and 4.0 compared to pH 3.0. A possible reason for the differences could be the used cultivation temperature for their experiments of 70 °C and that cultivations were performed in batch mode using a different medium.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…While there is broad consensus on the optimal growth temperature of S. acidocaldarius being at 75 °C [ 7 , 8 , 9 , 10 , 33 ] the described optimal cultivation pH still varies [ 5 , 6 , 7 , 8 , 9 , 10 ]. Our study determined a pH optimum of 3.0 in regards to the cell density during continuous cultivation ( Figure 2 ), contradicting the recent publication by Cobban et al [ 11 ], in which higher biomass yields were observed at pH 2.0 and 4.0 compared to pH 3.0. A possible reason for the differences could be the used cultivation temperature for their experiments of 70 °C and that cultivations were performed in batch mode using a different medium.…”
Section: Discussioncontrasting
confidence: 99%
“…Since the pH optimum of this organism is still disputed in literature and recently Cobban et al [ 11 ] showed data conflicting with the broad consensus of the optimal pH of 3 to 3.5 [ 5 , 6 , 7 , 8 , 9 , 10 ], we determined the pH optimum by shifting the pH from 2.0 to 4.0 in increments of 0.5 pH units at a constant growth temperature of 75 °C and dilution rate of 0.03 h −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of cyclization in GDGTs has successfully been used for reconstruction of sea surface temperature (SST), expressed in various SST proxies (Kim et al., 2010; Schouten et al., 2002; Wörmer et al., 2014). However, even though the sensitivity to temperature variations has been confirmed in pure culture experiments (Elling et al., 2015; Wuchter et al., 2004), studies investigating the effect of nutrient availability (Cobban et al., 2020; Evans et al., 2018; Hurley et al., 2016) and oxygen concentration (Cobban et al., 2020; Qin et al., 2015) also showed a strong response of the degree of cyclization. Additionally, the potential input of GDGTs from a second archeal clade, the Euryarchaeota of Marine Group II (MG II), possibly affects the GDGT signal exported to sediments.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of cyclization in isoGDGTs is a key strategy for archaea to adapt to extreme environments, with more cyclopentyl moieties generally produced by archaea growing at a higher temperature or a lower pH (47)(48)(49). Molecular modeling suggests that an increase in isoGDGT cyclization degree leads to tighter membrane packing that enhances membrane thermal stability and reduces overall membrane permeability (50,51).…”
Section: The Physiological Function Of Methylation and Cyclization In...mentioning
confidence: 99%